The postfigurative Christ in Morley Callaghan's Such is my beloved - F. Hale (Acta Theologica)
Symbolic Christ figures, i.e. characters whose lives to greatly varying extents mirror those of Jesus of Nazareth without being fully fledged allegories thereof, were frequently employed as fictional devices in nineteenth- and twentieth-century literature as means of expressing diverse qualities, lessons, mores, and values in the modern world. One esteemed literary artist who made use of this technique was the Canadian liberal Roman Catholic layman Morley Callaghan (1903-1990). In his novel of 1934, Such Is My Beloved, the protagonist, a gifted young priest in a major city, is a latter-day reflection of Christ. In this embodiment, Social Gospel aspects of Christianity come to the fore.